2016
DOI: 10.18632/oncotarget.11359
|View full text |Cite
|
Sign up to set email alerts
|

Elevated O-GlcNAcylation promotes gastric cancer cells proliferation by modulating cell cycle related proteins and ERK 1/2 signaling

Abstract: O-GlcNAc transferase (OGT) is the only enzyme in mammals that catalyzes the attachment of β-D-N-acetylglucosamine (GlcNAc) to serine or threonine residues of target proteins. Hyper-O-GlcNAcylation is becoming increasingly realized as a general feature of cancer and contributes to rapid proliferation of cancer cells. In this study, we demonstrated that O-GlcNAc and OGT levels were increased in all six gastric cancer (GC) cell lines as compared with immortal gastric epithelial cells. Downregulation of the O-GlcN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…Clinical studies have also found that higher levels of O‐GlcNAcylation are involved in the malignant clinicopathological features of various cancer patients . In gastric carcinoma, poorly differentiated tumours (grades II and III) showed significantly higher expression of O‐GlcNAcylation than grade I tumours . At the same time, we detected the expression of O‐GlcNAcylation and DDX5 in colorectal cancer tissues and matched normal controls.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Clinical studies have also found that higher levels of O‐GlcNAcylation are involved in the malignant clinicopathological features of various cancer patients . In gastric carcinoma, poorly differentiated tumours (grades II and III) showed significantly higher expression of O‐GlcNAcylation than grade I tumours . At the same time, we detected the expression of O‐GlcNAcylation and DDX5 in colorectal cancer tissues and matched normal controls.…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, we speculate that OGT regulation of DDX5 may be post‐transcriptional regulation. We used YinOYang 1.2 Server (www.cbs.dtu.dk/services/YinOYang) to predict the presence of O‐GlcNAcylation sites in DDX5, suggesting that DDX5 can be directly modified by O‐GlcNAcylation (Figure D). Therefore, we detected the stable binding products of OGT and DDX5 by co‐IP.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these previous studies, we indicated that modulating expression of miR-483 could influence total protein O-GlcNAcylation levels in gastric cancer cells. OGT has been reported to consistently increase in a wide variety of human cancers including gastric cancer and is involved in the initiation and development of cancers by enhancing cell proliferation and invasion [29][30][31]. However, the mechanism through which OGT is maintained at a high expression level in cancer cells remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the migrating and invasive capability of HepG2 is heightened by elevated O-GlcNAcylation, because this modification decreases E-cadherin expression and increases MMP-1, MMP-2 and MMP-3 expression [36]. OGT mRNA level and protein O-GlcNAc modification are progressively increased during the carcinogenesis of gastric cancer, and patients with hyper-O-GlcNAcylation have poor prognosis [37,38,99]. Reduction of O-GlcNAcylation by OGT siRNA inhbits and increment of this modification by OGA inhibitors enhances cell proliferation and tumor growth of gastric cancer through regulating the activation of ERK signaling pathway and the expression of CDK-2 and cyclin D1 [37].…”
Section: Altered Levels Of Ogt and O-glcnacylation In Cancers And Thementioning
confidence: 99%
“…Given the myriad functions concerned with O-GlcNAcylation, it is exceedingly reasonable that this posttranslational modification plays a fundamental role in the etiology of tumors [6,14,[26][27][28]. Indeed, O-GlcNAcylation is deregulated in many cancer types, including breast [29,30], pancreatic [31], prostate [32,33], colorectal [34,35], lung [34], liver [36], gastric [37,38], laryngeal [39], bladder [40], endometrial [41], esophageal squamous cell carcinoma [42], and nonsolid cancers such as chronic lymphocytic leukemia [43], and contributes to cancer cell metabolic reprogramming, cell proliferation, survival, angiogenesis, invasion, metastasis and cancer cell epigenetics [14,44].…”
Section: Introductionmentioning
confidence: 99%